2023
DOI: 10.20517/mrr.2022.23
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota resilience and recovery after anticancer chemotherapy

Abstract: Although research on the role of the gut microbiota (GM) in human health has sharply increased in recent years, what a “healthy” gut microbiota is and how it responds to major stressors is still difficult to establish. In particular, anticancer chemotherapy is known to have a drastic impact on the microbiota structure, potentially hampering its recovery with serious long-term consequences for patients’ health. However, the distinguishing features of gut microbiota recovery and non-recovery processes are not ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These differences initially present may contribute to the overall structure and function of the microbiome, as variations in carbohydrate, amino acid, energy, cofactor, and vitamin metabolism were significantly different at the baseline between the HuM1Rag and HuM2Rag mice. Therefore, based on these initial differences, perturbations via TMP-SMX and dexamethasone treatment may alter the HuM1Rag and HuM2Rag microbial ecosystem, affecting functionality, structure, and recovery [50,51]. Previously noted recovery from an antibiotic regime is dependent on the individual, which indicates that the baseline microbiota present in the HuM1Rag and HuM2Rag mice will affect microbial resistance and recovery [50,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…These differences initially present may contribute to the overall structure and function of the microbiome, as variations in carbohydrate, amino acid, energy, cofactor, and vitamin metabolism were significantly different at the baseline between the HuM1Rag and HuM2Rag mice. Therefore, based on these initial differences, perturbations via TMP-SMX and dexamethasone treatment may alter the HuM1Rag and HuM2Rag microbial ecosystem, affecting functionality, structure, and recovery [50,51]. Previously noted recovery from an antibiotic regime is dependent on the individual, which indicates that the baseline microbiota present in the HuM1Rag and HuM2Rag mice will affect microbial resistance and recovery [50,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The prebiotic and gut microbiota modulating effects of lactoferrin have also been evaluated in both healthy individuals and those suffering from various pathologies or undergoing therapies. Indeed, pathogenic gut dysbiosis has been observed during diverse therapies, including anticancer chemotherapy [ 164 ], and various diseases, including cancer and HIV infection, and it has often been associated with disease progression [ 165 , 166 ]. Results from some clinical trials suggested that lactoferrin may provide an adjunctive therapy to accelerate the process of gut microbiota restoration, thereby improving health outcomes and the response to therapy.…”
Section: Prebiotic Activity Of Whey Proteinsmentioning
confidence: 99%